Comparative feasibility of two World Health Organization partographs to predict prolonged labour: a randomized control trial - Rajoriya, Mohini; Kalra, Ruchi (International Journal of Clinical Trials, 2019)
Background: One of the major causes of maternal mortality is obstructed labor. Identification of abnormal labor at earliest and timely management can prevent prolonged labor and significantly reduce its sequel. Partograph is a useful tool in hands of labor care givers to monitor labor course. The study was done to compare feasibility of two WHO partographs a composite partograph including the latent phase with a simplified one without the latent phase to predict prolonged labor in randomized control trial. Methods: A randomized controlled trial, with parallel arm design was conducted. Sample size was calculated as 404 pregnant women .They were randomly categorized in two groups, each group having 202 participants. Results: labor had crossed the alert line in 108 (53.4%) cases monitored by composite partograph and 38(18.8%) cases monitored with simplified partograph. The calculated P value was <0.0001. The odds ratio calculate was 4.95 and 95% confidence interval was 3.16 to 7.76. Labor crossing the action line was found in 16 (7.9%) in composite partograph whereas in simplified partograph, labor had crossed the action line in 18 cases in simplified group. Calculated P value was 0.72 (>0.05). The odds ratio was 0.8793 and 95% confidence interval 0.43 to 1.77 which was not significant statistically .Most participants (70%) experienced difficulty with the composite partograph, but no participant reported difficulty while plotting the simplified partograph. Conclusions: WHO simplified partograph was found to be as good as WHO composite partograph in identifying maternal and perinatal outcomes and was more user friendly.